Perceptions of Restrictiveness in Forensic Mental Health: Do Demographic, Clinical, and Legal Characteristics Matter? - Tomlin, Jack (International journal of offender therapy and comparative criminology, 2020)
Where safe, forensic mental health systems should provide care in the least restrictive environment possible. Doing so can maximize patient autonomy and empowerment while minimizing unnecessary social disconnection and stigmatization. This study investigated whether patients’ perceptions of restrictiveness were associated with demographic, clinical, and legal characteristics. The Forensic Restrictiveness Questionnaire (FRQ) was used to measure perceptions of restrictiveness in 235 patients in low-, medium-, and high-secure settings in England. The results showed that restrictiveness scores were significantly higher for patients who experienced an adverse event in the past week or were diagnosed with a personality disorder compared to those with a mental illness. A regression analysis suggested that only diagnosis was predictive of FRQ scores when controlling for perceptions of ward atmosphere and quality of life. Age, length of stay, ethnicity, level of security, legal section, and offence type were not associated with FRQ scores. Future research should investigate the roles that individual symptoms, insight into illness, mood, personality, and expectations of care have in influencing perceptions of restrictiveness.